Relationship between Radiation Doses with Anthropometric Characteristics during Cardiac Catheterization Procedures in Iraqi Patients with Ischemic Heart Disease (Medical Forum Monthly, 2025)
Objective: To investigate relationship between radiationdose received during cardiac catheterization and patients’ anthropometric characteristics, particularly body mass index.Study Design: A cross-sectional studyPlace and Duration of Study: This study was conducted at the Single plane catheterization laboratory at Ibn-Al- Bittar-Centre-Baghdad/Iraq from 1st May 2024 31st August 2024.Methods: This is a cross-sectional, study with prospective data collection; cardiac-catheterization was done in Single-plane catheterization laboratory at Ibn-Al-Bittar-Centre-Baghdad/Iraq vide letter No. 478 dated 30th April2024 and 110 patients were enrolled.Results: There were 39 females and 71 males. 63.6% underwent coronary angiography and 36.4%underwent percutaneous coronary intervention. The mean age was 58.6 years and body mass index was 30.3±4.9kg/m2. Themean dose area product by body mass index group was 19.3, 65.6, 66.1, 112.3, 92.2and 52.1Gy·cm2, respectively. The corresponding mean kinetic energy released perunitmass (KERMA) values were: 277.7, 878.2, 1102.4, 1606.8, 1719.9, and 850.9mGy, respectively. Normality tests for both kinetic energy released per unit mass and dose-area- product showed significant differences across body mass index group(p<0.05), indicating that radiation dose data were not normally distributed. However, ANOVA tests showed no statistically significant differences in dose-area- product (p=0.415) or kinetic energy released per unit mass (p=0.580) among age groups.Conclusion: There is a clear association between body mass index and radiation dose. Higher body mass index levels are linked with increased kinetic energy released per unit mass and dose area product values.